Integral environmental protection in John Paul’s II teaching - Bołoz, Wojciech (Studia Ecologiae et Bioethicae, 2008)
In his teaching John Paul II paid a lot of attention to the subject of environmental protection. His holistic concept incorporates the most important issues that relate to preservation of natural resources that still exist. Among many issues discussed by him the following seem to be of the highest importance. The ecological issue refers to all people irrespective of religious or political views. Natural environment degradation bears negative consequences which apply to everyone, the Pope regards his comments on the natural environment protection as the Church’s support for the peoples’ efforts in overcoming the growing ecological crisis. In John Paul’s II opinion, so-called “anthropological mistake” is the basis for thoughtless degradation of natural environment. A human being who discovers his ability to transform and, to some extent, to create the world through his own work believes he can disobediently rule the Earth and bring it under his absolute control. He acts as if the Earth did not have its own shape nor an intention previously indicated by God. God’s intention for the Earth may indeed be expanded by a human but it should not be fought against. Instead of being God’s co-worker in the act of creation a human tries to replace Him. As a consequence, nature, which is oppressed rather than ruled by a human, protests. Ecological crisis is seen as a consequence of troubled relationship between a human and nature. In this relationship a human is driven only by his own economical needs. He does not take into consideration the specificity of nature’s constituting components: natural resources, plants and animals. Another important reason for the environment crisis is inconsiderate output of natural resources as if they were to last forever. Natural environment exploitation is reprehensible. However, destruction of “human environment” is equally dangerous. Alike with the Earth, which should be used respectfully in accordance with its initial intention, a human ought to value his own “natural and moral construction he was equipped with”. According to the teaching of the Church, God gave the Earth with everything it consists for the use of all the people and nations, this sense of common property also bears common responsibility for the existing goods. Because it is a shared property, it should be of a public concern, therefore , every enterprise that makes use of natural resources is obliged to take care of the environment.